Manajemen Komunikasi Badan Penanggulangan Bencana Daerah dalam Penanggulangan Bencana Banjir di Kabupaten Tolitoli - Wulan, Sri Nawang; Herawati, Andi Febri; Alfiyaty, Rizqy (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study aims to find out how BPBD Tolitoli Regency's communication management. In addition, in handling disasters using qualitative descriptive methods with the theory of Puji Lestari in Susanto et al. and collecting data through observation, personal interviews and structured, and documented. This study used a purposive sampling method by taking four informants. The results of this study indicate that the Tolitoli Regency Regional Disaster Management Agency carried out the stages in accordance with the Law of the Republic of Indonesia number 24 of 2007 concerning disaster management. In the communication management plan, they carry out pre-disaster and post-disaster stages. They themselves have their own organizing and duties in disaster management. Then from disaster management planning and evaluation they always coordinate cooperation with relevant stakeholders. Self-evaluation in the event of a disaster they make into an action plan report that is the gradual development of the area of the disaster incident. For the inhibiting factors we saw that BPPD has problems related to difficult communication networks for remote areas and budgets for disaster management as well as a lack of infrastructure which is an obstacle to BPBD activities in flood disaster management.